Lipid Profiles and Cardiovascular Risk in Patients with Oral Lichen Planus - Tomislav Radic; Livia Cigic; Ana Glavina; Ana Hrboka; Ana Druzijanic; Ivona Musa Leko; Dolores Biocina-Lukenda (MDPI AG, 2022)
Background: It has been reported that dyslipidemia prevalence and cardiovascular disease risk were increased in subjects with oral lichen planus diagnose. On the other hand, so far, there is no available data on the topic of cardiovascular risk (CVR) in subjects with oral lichen planus (OLP). The main aim of this study, due to lack of any other study covering this topic, was to investigate lipid profile and assess CVR in patients with OLP. Materials and Methods: To create a routine lipid profile, we collected triglyceride serum levels, total cholesterol, low-density lipoprotein cholesterol, and high-density lipoprotein cholesterol from 63 OLP patients and 63 healthy people representing control subjects. For every patient their individual cardiovascular risk was measured. Results: In comparison with the tested control subjects, patients with OLP had all parameters of the lipid profile elevated, with no differences of statistical importance. Furthermore, the experimental (OLP) and control groups shared similar mean values of the lipid profile parameters. Conclusions: The association of OLP with cardiovascular risk was not established and further studies with more subjects involved are required to validate this connection.